Which factors govern the adsorption of peptides to Zr(iv)-based metal–organic frameworks?. Issue 5 (9th February 2022) - Loosen, Alexandra; de Azambuja, Francisco; Parac-Vogt, Tatjana N.
Abstract : An adsorption study of dipeptides onto different Zr-based metal–organic frameworks (Zr-MOF) unravelled key parameters affecting peptide-MOF interactions in aqueous conditions, and provides unique molecular insights for future designs. Abstract : Fundamental insight into the interactions between biological molecules and materials is essential for the design and development of adsorbents for many applications. Herein, we use a range of peptides to study the nature of these interactions and identify parameters pertinent to their adsorption onto Zr-based metal–organic framework (MOF) materials differing in structure and surface properties. A combination of experimental techniques revealed that MOF characteristics such as available Zr(iv ) sites, nature of the linker, and hydrophilicity had a large influence on peptide adsorption. Experiments with peptides protected at N- and C-terminals indicated that adsorption to more hydrophilic MOFs MOF-808 and UiO-66 is governed by C-terminal carboxylate coordination to the Zr6 cluster, while adsorption onto the more hydrophobic NU-1000 is driven by electrostatic repulsion of the N-terminal group and hydrophobic interactions with the MOF surface/linker. Systematic variation in the amino acid's side chain suggests that other interactions like hydrophobic, aromatic, sulfur– or cation–π, and carboxylate interactions also influence adsorption, mostly arising from the hydrophobic/aromatic nature of the linkers and Zr6 cluster connectivity. Furthermore, the adsorption of peptides was strongly dependent on the pH of the solution, which could be used to modulate the affinity of the MOF material towards peptides. These results provide unique molecular insight towards understanding adsorption of biomolecules onto MOF materials and their design as nanozymes for catalytic reactions with peptides and proteins.